DAMPAK BELANJA PEMERINTAH DAERAH TERHADAP PEMBANGUNAN EKONOMI INKLUSIF DI PROVINSI SULAWESI TENGAH - Apri Prayoga Arrfah; Syafri Syafri (JURNAL INFO ARTHA, 2022)
The background of this research is the high average GRDP (Gross Regional Domestic Product) growth in Central Sulawesi Province in the last decade, but the province also has a high poverty rate. Therefore, this research was conducted to measure and analyze the inclusiveness of economic development and its determinants from the aspect of government intervention in the form of local government spending. The research method used is panel data regression with FEM (fixed effect model) from 10 regencies/cities in Central Sulawesi from 2011 to 2020. The results of the study showed that regional government spending on housing and public facilities functions has a positive and significant effect on inclusive economic development, while local government spending on education and social protection functions has a positive but not significant effect on inclusive economic development